SYTL3–SLC22A3 Single-Nucleotide Polymorphisms and Gene–Gene/Environment Interactions on the Risk of Hyperlipidemia - Zheng, Peng-Fei; Yin, Rui-Xing; Cao, Xiao-Li; Guan, Yao-Zong; Deng, Guo-Xiong; Wei, Bi-Liu; Liu, Chun-Xiao (Frontiers in Genetics, 2021)
The current study aims to further delineate the associations between the synaptotag-min like 3 (SYTL3) and solute carrier family 22 member 3 (SLC22A3) SNPs and their haplotypes, gene-gene (G × G)/environment (G × E) interactions on the risk of hy-perlipidaemia (HLP) in the Maonan and Han ethnic groups. Genotype distribution amongst the SYTL3-SLC22A3 SNPs in 2829 individual patients bearing no relation-ship to each other (Han, 1436; Maonan, 1393) was analyzed utilizing next-generation sequencing techniques. The genotype frequencies of the rs6455600, rs2129209 and rs446809 SNPs were varied between two ethnic groups (P < 0.05-0.001). Various SNPs were correlated with serum levels of triglyceride (TG; rs446809), total choles-terol (TC; rs6455600, rs2129209 and rs539298) and low-density lipoprotein choles-terol (LDL-C; rs446809) amongst the Han population, whereas those were correlated with TC (rs6455600, rs539298), TG (rs446809) and LDL-C (rs446809) levels in Maonan ethnic group (P < 0.008-0.001). One part of haplotypes resulted in worsened HLP-related morbidity in the Han (SYTL3 A-C-A-A, SLC22A3 A-A, A-G and SYTL3-SLC22A3 A-C-A-A-A-A, A-C-A-A-A-G) and Maonan (SYTL3 A-C-A-A, SLC22A3 A-A, A-G, SYTL3-SLC22A3 A-C-A-A-A-A, G-T-C-A-A-A and G-T-C-A-C-A) ethnic groups, whereas another part of haplotypes lowered HLP-related health risks in the Han (SLC22A3 C-A, C-G, SYTL3-SLC22A3 A-C-A-A-C-A, A-C-A-A-C-G, and G-T-C-A-C-A) and Maonan (SLC22A3 C-G, SYTL3-SLC22A3 A-C-A-A-C-G) ethnic groups. We discovered that the SYTL3-SLC22A3 SNPs and their haplotypes were associated with serum lipid levels and the risk of HLP in our studied populations.